She shoots to conquer - Cannell, Dorothy (Minotaur Books, 2009)
Lord Belfrey of Mucklesfeld Manor has decided to save his crumbling establishment by offering himself as the prize on a TV reality show, but after one of his potential brides is shot during an archery contest, Ellie Haskell begins to explore the dark passageways and hidden nooks of Belfrey's delightfully Gothic estate--unprepared for the secrets lurking behind closed doors.